Chapter Modellazione semantica HBIM per la rappresentazione digitale dell’intervento sul patrimonio esistente - Raco, Fabiana; Balzani, Marcello; Planu, Fabio; Tasselli, Nicola (FrancoAngeli, 2022)
The 43rd UID conference, held in Genova, takes up the theme of ‘Dialogues’ as practice and debate on many fundamental topics in our social life, especially in these complex and not yet resolved times. The city of Genova offers the opportunity to ponder on the value of comparison and on the possibilities for the community, naturally focused on the aspects that concern us, as professors, researchers, disseminators of knowledge, or on all the possibile meanings of the discipline of representation and its dialogue with ‘others’, which we have broadly catalogued in three macro areas: History, Semiotics, Science / Technology. Therefore, “dialogue” as a profitable exchange based on a common language, without which it is impossible to comprehend and understand one another; and the graphic sign that connotes the conference is the precise transcription of this concept: the title ‘translated’ into signs, derived from the visual alphabet designed for the visual identity of the UID since 2017. There are many topics which refer to three macro sessions: - Witnessing (signs and history) - Communicating (signs and semiotics) - Experimenting (signs and sciences) Thanks to the different points of view, an exceptional resource of our disciplinary area, we want to try to outline the prevailing theoretical-operational synergies, the collaborative lines of an instrumental nature, the recent updates of the repertoires of images that attest and nourish the relations among representation, history, semiotics, sciences.